CHEMISTRY AND ITS SOCIAL SIGNIFICANCE (Web of Teachers: Inderscience Research, 2025)
This article analyzes the role and social significance of chemistry in society. Chemistry plays an important role not only in the field of natural science, but also in economics, health, ecology and everyday life. The article discusses the impact of chemistry on social life, its practical application and future opportunities.